Editorial - Pasierbek, Wit (Horyzonty Wychowania, 2017)
Freedom is deeply ingrained in the heart and desires of everyman. And as a rational being, endowed with free will, he hasan ability to decide and control his own conduct, having thepossibility to choose between good and evil. Furthermore, humandignity is determined by his inalienable right to be free andautonomous in his decisions. The aim of freedom understoodin this way is aspiration for man’s happiness and self-realization.